Analysis of Spatial Distribution and Factors Influencing the Location of Tofu and Tempe Traders in the Periphery Area Market of Surakarta City in Supporting the Achievement of the SDGs - Sunariya, M Iqbal Taufiqurrahman; Danardono, Danardono; Fikriyah, Vidya Nahdhiyatul; Arini, Maya Intan; Sulistyoningsih, Putri; Faridah, Rahma Afifah Nur; Ditasari, Sinta Rahma; Salsabilla, Tiara Zahra; Ardana, Viennara Zahwa Gladies (International Journal for Disaster and Development Interface, 2024)
Peripheral areas are areas on the outskirts of a city that usually have the structure and characteristics of a combination of village and city, both socially, physically, economically, and culturally. The outskirts of Surakarta City include the surrounding regency i.e., Sukoharjo, Boyolali, Karanganyar, Wonogiri, Klaten, and Sragen Regency. These areas have potential tofu and tempeh industry. This research was conducted to determine the spatial distribution patterns and factors influencing the location of tofu and tempeh traders. Data was collected using a questionnaire and analyzed using the average nearest-neighbor pattern. The results show that the spatial distribution pattern is dispersed. Dispersed means that each area is evenly distributed and far from other areas. This happens because the ANN (Average Nearest Neighbor) value is >1. The influencing factor for the location of tofu and tempeh traders in the markets is the location chosen relatively close to where tofu and tempeh traders live so that the distance is not too far. The location was chosen because it has been running a business for generations. The location has good facilities and cleanliness, making it comfortable to carry out buying and selling transactions. This place is busy with buyers from various regions